(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND The cause of coronavirus disease 2019 (COVID-19) is severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Clinical information about patients undergoing lung resection while infected with this virus and pathological information about early COVID-19 pneumonia are still scarce. CASE PRESENTATION A 69-year-old male patient underwent a right pneumonectomy for squamous cell lung carcinoma. Until the fourth postoperative day, the patient, who had minor radiological changes on chest x-ray, was asymptomatic. From this day, the COVID-19 test, which was performed after the appearance of symptoms such as fever and shortness of breath, lymphopenia and diffuse ground glass opacity in the left lung on computed tomography, was reported to be positive. The patient was given NIMV (non-invasive mechanical ventilation), and hydroxychloroquine, favipiravir and azithromycin in isolation intensive care, with the diagnosis of severe pneumonia. He was discharged on the 17th postoperative day with healing of the lung lesions. The pathology specimen of the patient, who was found to have been infected with SARS-CoV-2 before the day of surgery, was examined retrospectively. Irregular and severe pneumocyte hyperplasia, interstitial thickening, oedema, pronounced protein exudates, diffuse enlargement of the alveolar walls, macrophage infiltration and fibroblastic proliferation, which is an indicator of early organisation, were detected. CONCLUSION We believe that the clinical course and pathology findings obtained after right pneumonectomy in a patient with pre-symptomatic COVID-19 pneumonia will guide the diagnosis and treatment of patients infected with SARS-CoV-2.